2020
DOI: 10.1002/mds3.10142
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of PDMS substrates for tumour cell adhesion: Influence of roughness parameters

Abstract: Surface properties play a key role in how biomaterials interact with the environment. Surface topography has also been reported to be influential in some research, although its effect is still not well elucidated. In this study, nano-roughened polydimethylsiloxane (PDMS) substrates were developed through a chemically etched intermediate surface. Additionally, PDMS substrates containing 10-30 μm diameter micropillars were functionalized with multilayers of chitosan (CHI) and hyaluronic acid (HA) via layer-by-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…[ 64 ] The chitosan coating on the PDMS substrate has the lowest surface roughness (79 ± 12 nm, Figure S1b, Supporting Information). Similar surface morphology was reported [ 65–66 ] with roughness values ≈1 nm using water‐based deposition. The surface roughness of the chitosan coating on PET substrate is 138 nm ± 33 nm (Figure S1c, Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…[ 64 ] The chitosan coating on the PDMS substrate has the lowest surface roughness (79 ± 12 nm, Figure S1b, Supporting Information). Similar surface morphology was reported [ 65–66 ] with roughness values ≈1 nm using water‐based deposition. The surface roughness of the chitosan coating on PET substrate is 138 nm ± 33 nm (Figure S1c, Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…Silicone surfaces are typically first treated with oxygen plasma followed by grafting of carboxylic acid functional groups to create a charged surface that can support formation of the LbL coating. Several studies have reported silicones with LbL coatings comprised of alternating layers of hyaluronic acid (HA) and a polycation (e.g., chitosan and poly- l -lysine). The resulting LbL-modified silicone surfaces displayed significant improvement in hydrophilicity as well as a decrease in cell adhesion. Unfortunately, charged layers of LbL coatings may be susceptible to rearrangement or delamination, as well as increase interactions with proteins .…”
Section: Surface Modificationsmentioning
confidence: 99%
“…For instance, 3D-printed electrodes provide versatility in the geometry and functionality of electrochemical sensors. The electrochemical transduction elements normally contain noble metals (gold, silver, platinum), carbon, or organic and inorganic semiconductors [ 46 ], and 3D printing allows for controlling the sensor surface properties to maximize tumor cell adhesion [ 47 , 48 ]. Hence, with 3D printing, it is possible to improve the selectivity and sensitivity of biosensing platforms.…”
Section: Three-dimensionally Printed Sensors For Cancer Diagnosismentioning
confidence: 99%